Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure, let's prove the logical equivalence [tex]\(( p \wedge q ) = \sim ( p \rightarrow \sim q )\)[/tex] using a truth table.
To do this, we will construct a truth table that includes columns for [tex]\(p\)[/tex], [tex]\(q\)[/tex], [tex]\(p \wedge q\)[/tex], [tex]\(\sim q\)[/tex], [tex]\(p \rightarrow \sim q\)[/tex], and [tex]\(\sim ( p \rightarrow \sim q )\)[/tex].
Here's the detailed step-by-step solution:
1. List the possible truth values for [tex]\(p\)[/tex] and [tex]\(q\)[/tex]:
There are four combinations of truth values for [tex]\(p\)[/tex] and [tex]\(q\)[/tex]:
- [tex]\(p = \text{False}, q = \text{False}\)[/tex]
- [tex]\(p = \text{False}, q = \text{True}\)[/tex]
- [tex]\(p = \text{True}, q = \text{False}\)[/tex]
- [tex]\(p = \text{True}, q = \text{True}\)[/tex]
2. Calculate [tex]\(p \wedge q\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & p \wedge q \\ \hline \text{False} & \text{False} & \text{False} \\ \text{False} & \text{True} & \text{False} \\ \text{True} & \text{False} & \text{False} \\ \text{True} & \text{True} & \text{True} \\ \hline \end{array} \][/tex]
3. Calculate [tex]\(\sim q\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & \sim q \\ \hline \text{False} & \text{False} & \text{True} \\ \text{False} & \text{True} & \text{False} \\ \text{True} & \text{False} & \text{True} \\ \text{True} & \text{True} & \text{False} \\ \hline \end{array} \][/tex]
4. Calculate [tex]\(p \rightarrow \sim q\)[/tex]:
Recall that [tex]\(p \rightarrow \sim q\)[/tex] is equivalent to [tex]\(\neg p \lor \sim q\)[/tex].
[tex]\[ \begin{array}{|c|c|c|c|} \hline p & q & \sim q & p \rightarrow \sim q \\ \hline \text{False} & \text{False} & \text{True} & \text{True} \\ \text{False} & \text{True} & \text{False} & \text{True} \\ \text{True} & \text{False} & \text{True} & \text{True} \\ \text{True} & \text{True} & \text{False} & \text{False} \\ \hline \end{array} \][/tex]
5. Calculate [tex]\(\sim ( p \rightarrow \sim q )\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|c|} \hline p & q & p \rightarrow \sim q & \sim ( p \rightarrow \sim q ) \\ \hline \text{False} & \text{False} & \text{True} & \text{False} \\ \text{False} & \text{True} & \text{True} & \text{False} \\ \text{True} & \text{False} & \text{True} & \text{False} \\ \text{True} & \text{True} & \text{False} & \text{True} \\ \hline \end{array} \][/tex]
6. Compare [tex]\(p \wedge q\)[/tex] with [tex]\(\sim ( p \rightarrow \sim q )\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|c|} \hline p & q & p \wedge q & \sim ( p \rightarrow \sim q ) \\ \hline \text{False} & \text{False} & \text{False} & \text{False} \\ \text{False} & \text{True} & \text{False} & \text{False} \\ \text{True} & \text{False} & \text{False} & \text{False} \\ \text{True} & \text{True} & \text{True} & \text{True} \\ \hline \end{array} \][/tex]
From the table, we can see that the truth values for [tex]\(p \wedge q\)[/tex] and [tex]\(\sim ( p \rightarrow \sim q )\)[/tex] are always identical for all possible combinations of [tex]\(p\)[/tex] and [tex]\(q\)[/tex]. Hence, it is proven through the truth table that:
[tex]\[ ( p \wedge q ) = \sim ( p \rightarrow \sim q ) \][/tex]
This completes the proof of the logical equivalence.
To do this, we will construct a truth table that includes columns for [tex]\(p\)[/tex], [tex]\(q\)[/tex], [tex]\(p \wedge q\)[/tex], [tex]\(\sim q\)[/tex], [tex]\(p \rightarrow \sim q\)[/tex], and [tex]\(\sim ( p \rightarrow \sim q )\)[/tex].
Here's the detailed step-by-step solution:
1. List the possible truth values for [tex]\(p\)[/tex] and [tex]\(q\)[/tex]:
There are four combinations of truth values for [tex]\(p\)[/tex] and [tex]\(q\)[/tex]:
- [tex]\(p = \text{False}, q = \text{False}\)[/tex]
- [tex]\(p = \text{False}, q = \text{True}\)[/tex]
- [tex]\(p = \text{True}, q = \text{False}\)[/tex]
- [tex]\(p = \text{True}, q = \text{True}\)[/tex]
2. Calculate [tex]\(p \wedge q\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & p \wedge q \\ \hline \text{False} & \text{False} & \text{False} \\ \text{False} & \text{True} & \text{False} \\ \text{True} & \text{False} & \text{False} \\ \text{True} & \text{True} & \text{True} \\ \hline \end{array} \][/tex]
3. Calculate [tex]\(\sim q\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|} \hline p & q & \sim q \\ \hline \text{False} & \text{False} & \text{True} \\ \text{False} & \text{True} & \text{False} \\ \text{True} & \text{False} & \text{True} \\ \text{True} & \text{True} & \text{False} \\ \hline \end{array} \][/tex]
4. Calculate [tex]\(p \rightarrow \sim q\)[/tex]:
Recall that [tex]\(p \rightarrow \sim q\)[/tex] is equivalent to [tex]\(\neg p \lor \sim q\)[/tex].
[tex]\[ \begin{array}{|c|c|c|c|} \hline p & q & \sim q & p \rightarrow \sim q \\ \hline \text{False} & \text{False} & \text{True} & \text{True} \\ \text{False} & \text{True} & \text{False} & \text{True} \\ \text{True} & \text{False} & \text{True} & \text{True} \\ \text{True} & \text{True} & \text{False} & \text{False} \\ \hline \end{array} \][/tex]
5. Calculate [tex]\(\sim ( p \rightarrow \sim q )\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|c|} \hline p & q & p \rightarrow \sim q & \sim ( p \rightarrow \sim q ) \\ \hline \text{False} & \text{False} & \text{True} & \text{False} \\ \text{False} & \text{True} & \text{True} & \text{False} \\ \text{True} & \text{False} & \text{True} & \text{False} \\ \text{True} & \text{True} & \text{False} & \text{True} \\ \hline \end{array} \][/tex]
6. Compare [tex]\(p \wedge q\)[/tex] with [tex]\(\sim ( p \rightarrow \sim q )\)[/tex]:
[tex]\[ \begin{array}{|c|c|c|c|} \hline p & q & p \wedge q & \sim ( p \rightarrow \sim q ) \\ \hline \text{False} & \text{False} & \text{False} & \text{False} \\ \text{False} & \text{True} & \text{False} & \text{False} \\ \text{True} & \text{False} & \text{False} & \text{False} \\ \text{True} & \text{True} & \text{True} & \text{True} \\ \hline \end{array} \][/tex]
From the table, we can see that the truth values for [tex]\(p \wedge q\)[/tex] and [tex]\(\sim ( p \rightarrow \sim q )\)[/tex] are always identical for all possible combinations of [tex]\(p\)[/tex] and [tex]\(q\)[/tex]. Hence, it is proven through the truth table that:
[tex]\[ ( p \wedge q ) = \sim ( p \rightarrow \sim q ) \][/tex]
This completes the proof of the logical equivalence.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.